Multicultural da’wah strategy: An inclusive approach in promoting tolerance and social harmony in plural societies - Setiawan, Donny (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study examines Habib Husein Ja'far Al-Hadar's multicultural da'wah strategy, focusing on inclusivity and tolerance in Indonesia's plural society. His approach uses constructive dialogue, social media, and cultural adaptation to reach diverse audiences, promoting interfaith tolerance and social harmony. However, it faces criticism from traditionalists regarding potential distortions of Islamic values. Methods: This study uses a qualitative approach with a case study method to analyze Habib Jafar's multicultural da'wah strategy, focusing on his communication with diverse audiences. Data is collected through in-depth interviews, content analysis of his speeches and social media, and participatory observation of his preaching activities. Thematic analysis, grounded in intercultural communication and inclusive da'wah theories, is used to identify key patterns in his strategy and its impact on fostering tolerance and understanding in a pluralistic society. Findings: The results of the analysis reveal that Habib Husein's approach is not only relevant to the needs of modern society but is also able to integrate Islamic values in the context of pluralism. Multicultural da'wah strengthens the concept of rahmatan lil'alamin by fostering inclusive dialogue and promoting interfaith understanding. It bridges cultural and religious differences, creating unity and mutual respect. Conclusion: Thus, this multicultural da'wah strategy can be an effective model to be applied in other multicultural societies, in order to create peace and strengthen social relations. Novelty/Originality of This Study: By integrating digital media analysis with case study methods, this research highlights how modern da'wah can effectively adapt to cultural diversity while maintaining Islamic values, offering fresh insights into the intersection of religious outreach, social media, and multicultural engagement.